Environmental mobile monitoring of urban microclimates: A review. (November 2022) - Kousis, I.; Manni, M.; Pisello, A.L.
Abstract: Monitoring efficiently urban microclimates is necessary for rendering cities resilient against climate change impacts. Aiming to retrieve data of high spatial resolution, mobile monitoring techniques have been introduced and applied within various urban contexts around the globe. Mobile monitoring campaigns may indeed contribute toward a high-granularity evaluation of the intra-urban characteristics of each city. In addition, it can help exploit resiliency planning at different aggregation levels when implemented in conjunction with traditional monitoring systems, such as fixed stations and satellites. Under this scenario, this study presents for the first time a systematic and critical review of the recent and most comprehensive mobile monitoring systems, and the corresponding field campaigns and protocols followed. The reviewed monitoring systems are developed on either motorized (e.g. cars, vans) or non-motorized (e.g. bicycles, carts, humans) agents for measuring the main parameters regulating urban canopy layers with respect to the (i) hygrothermal environment, (ii) air quality, (iii) light pollution, (iv) noise pollution. Overall, 94 articles are analyzed for concluding to the current state of the art, the corresponding scientific gaps, and proposed future research paths. Most of the reported monitoring systems are developed to monitor only one environmental domain, while the lack of standardized monitoring protocols is found to be the biggest challenge that needs to be addressed for minimizing biases and rendering the outcomes of different studies comparable. Relevant technological advancements and human-centric frameworks are further discussed aiming to exploit mobile monitoring for establishing efficient decision-making and risk assessment within urban environments. Highlights: Systematic literature review of urban mobile monitoring is performed for the first time. Thermal environment, air quality, noise and light pollution monitoring protocols are reviewed. The review reports on monitoring campaigns performed at a global scale. The challenges and future paths for an efficient urban mobile monitoring are devised.